Eficacia de una nueva fitasa microbiana en dietas de cerdos en crecimiento - Leiva y Cols., Yoany (2018)
This research aimed to evaluate the effects of inclusion of a new phytase of bacterial origin in the feed of growing pigs, on apparent digestibility coefficient and retention of different nutrients. Five experimental diets differing in the addition of phytase and in phosphorus (P) content were used: positive control (C+) with 7.1g of total / kg P without phytase, negative control (C-) with low P (5.6 g total P/ kg) without phytase and three diets base don C- supplemented with 250, 500 and 1000 phytase units,UFT / Kg of feed. Seventy five male pigs (32.24 ± 2.77 kg live weight on average) were used, in five batches, each batch consisting of 15 pigs. The experimental period lasted 18 days, in each batch (7 days of adaptation to pen and feed, 7 days adaptation to digestibility cage and four days of collection of feces and urine – digestibility trial). In the conditions of this study, the addition of the new phytase in growing pigs at levels of 500 and 1000 UFT / kg produced an increase (p>0.05) in the digestibility of P in 5 to 9 percentage points and an increase in the retention of P in 5.4 and 10 percentage points, respectively compared with diets low in phosphorus and without phytase (C-). Other minerals were not affected by the addition of phytase.